Life satisfaction in spouses of stroke survivors and control subjects: A 7-year follow-up of participants in the Sahlgrenska Academy study on ischaemic stroke - Tamar Abzhandadze; Gunilla Forsberg-Wärleby; Lukas Holmegaard; Petra Redfors; Christina Jern; Christian Blomstrand; Katarina Jood (Medical Journals Sweden, 2017)
Objective: To investigate life satisfaction in spouses of middle-aged stroke survivors from the long-term perspective and to identify factors that explain their life satisfaction. Design: Cross-sectional, case-control study. Subjects: Cohabitant spouses of survivors of ischaemic stroke aged < 70 years at stroke onset (n = 248) and spouses of controls (n = 246). Methods: Assessments were made 7 years after inclusion to the study. Spouses' life satisfaction was assessed with the Fugl-Meyer's Life Satisfaction Check-List (LiSAT 11). Stroke-related factors were examined with the National Institutes of Health stroke scale, Mini-Mental State Examination, Barthel Index and modified Rankin Scale. Results: Spouses of stroke survivors had significantly lower satisfaction with general life, leisure, sexual life, partner relationship, family life, and poorer somatic and psychological health than spouses of controls. Caregiving spouses had significantly lower scores on all life domains except vocation and own activities of daily living than non-caregiving spouses. Spouses' satisfaction on different life domains was explained mainly by their age, sex, support given to the partner, and the survivor's level of global disability, to which both physical and cognitive impairments contributed. Conclusion: Seven years after stroke, spouses of stroke survivors reported lower life satisfaction compared with spouses of controls. Life satisfaction in stroke survivors' spouses was associated with spouses' age, sex, giving support, and the stroke survivors' level of global disability.